ANALYSIS OF TEMPE LEAF PROCESSING BUSINESS INCOME IN KUALA PESISIR DISTRICT, NAGAN RAYA REGENCY - Nurul Hidayati; Bagio Bagio (Jurnal Ekonomi, 2022)
Arongan Village, Kuala Pesisir District, is one of the areas that has an industrial processing of soybeans into tempeh, namely Tempe Super Dipta and Tempe Murni Mb Seunagan. The purpose of this study is to see how much income is generated. This location was chosen deliberately because the Village Development Program is related to the stunting prevention program. The method of determining the sample uses the census method, namely that all populations are used as research samples so that the samples used are as many as 2 attempts. The results obtained by the average revenue obtained is Rp. 2,880,000.00 per production period (6 days) and the income generated is Rp.760,927.09 per production period while for a month it is Rp. 3,043,708.35 per month. The BEP unit produced is 1,060 packs of banana leaf tempeh and the rupiah BEP is Rp. 1472.58.